Socially-Assistive Robots Using Empathy untuk Mengurangi Nyeri dan Distress selama Pemasangan IV Line Perifer pada Anak - Ray, Aina Aprilma; Rahman, La Ode Abdul (Universitas Fort De Kock Bukittinggi, 2021)
Background: Painful medical procedures such as insertion of a peripheral IV line in a child can have long-lasting effects, such as increased sensitivity to future painful stimuli, avoidance of medical treatment, or posttraumatic distress. In nursing science, pain reduction in children can be done by using distraction techniques. In the era of 4.0, the use of robots in helping nurse care is no stranger. Socially-Assistive Robots are a type of social robot that has been used in helping children with ASD, cancer, cerebral palsy and even the elderly. Objective: To provide an overview and ideas from the results of a literature review about the possibility of applying Socially-Assistive Robots Using Empathy to reduce pain and distress during peripheral IV line insertion in children. Discussion: From the results of the study and review of 12 selected journals, it is concluded that Socially-Assistive Robots Using Empathy is a technology that needs to be developed and applied. Recommendation: It is hoped that Socially-Assistive Robots Using Empathy will be present in Indonesia and future researchers can test its effectiveness. Keywords: Socially-Assistive Robots, pain, distress, IV line insertion